Impact of information technology on libraries - Panigrahi, R. M. (Ess Ess Pubications, 2000)
Contents of material: Library information networking. Impact of technology on libraries. Evaluation of technological advancement. A "Paperless society". Human factors in libraries. Competition and private-public sector reaction. Network level reactions